Structure, Sex, and Strength and Knee and Hip Kinematics During Landing - Howard, Jennifer S (The National Athletic Trainers' Association, Inc., 2011)
CONTEXT: Researchers have observed that medial knee collapse is a mechanism of knee injury. Lower extremity alignment, sex, and strength have been cited as contributing to landing mechanics. OBJECTIVE: To determine the relationship among measurements of asymmetry of unilateral hip rotation (AUHR); mobility of the foot, which we described as relative arch deformity (RAD); hip abduction–external rotation strength; sex; and me-dial collapse of the knee during a single-leg jump landing. We hypothesized that AUHR and RAD would be positively correlated with movements often associated with medial collapse of the knee, including hip adduction and internal rotation excursions and knee abduction and rotation excursions. DESIGN: Descriptive laboratory study. SETTING: Research laboratory. PATIENTS OR OTHER PARTICIPANTS: Thirty women and 15 men (age = 21 ± 2 years, height = 171.7 ± 9.5 cm, mass = 68.4 ± 9.5 kg) who had no history of surgery or recent injury and who participated in regular physical activity volunteered. INTERVENTIONS : Participants performed 3 double-leg forward jumps with a single-leg landing. Three-dimensional kinematic data were sampled at 100 Hz using an electromagnetic tracking system. We evaluated AUHR and RAD on the preferred leg and evaluated isometric peak hip abductor–external rotation torque. We assessed AUHR by calculating the difference between internal and external hip rotation in the prone position (AUHR = internal rotation – external rotation). We evaluated RAD using the Arch Height Index Measurement System. Correlations and linear regression analyses were used to assess relationships among AUHR, RAD, sex, peak hip abduction–external rotation torque, and kinematic variables for 3-dimensional motion of the hip and knee. MAIN OUTCOME MEASURE(S): The dependent variables were joint angles at contact and joint excursions between contact and peak knee flexion. RESULTS: We found that AUHR was correlated with hip adduction excursion (R = 0.36, P = .02). Asymmetry of unilateral hip rotation, sex, and peak hip abduction–external rotation torque were predictive of knee abduction excursion (adjusted R(2) = 0.47, P < .001). Asymmetry of unilateral hip rotation and sex were predictive of knee external rotation excursion (adjusted R(2) = 0.23, P = .001). The RAD was correlated with hip adduction at contact (R(2) = 0.10, R = 0.32, P = .04) and knee flexion excursion (R(2) = 0.11, R = −0.34, P = .03). CONCLUSIONS: Asymmetry of unilateral hip rotation, sex, and hip strength were associated with kinematic components of medial knee collapse.